2019
DOI: 10.1038/s41598-019-53728-8
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of lipid metabolism and appearance of slow myofiber-specific isoforms accompany the development of Wooden Breast myopathy in modern broiler chickens

Abstract: Previous transcriptomic studies have hypothesized the occurrence of slow myofiber-phenotype, and dysregulation of lipid metabolism as being associated with the development of Wooden Breast (WB), a meat quality defect in commercial broiler chickens. To gain a deep understanding of the manifestation and implication of these two biological processes in health and disease states in chickens, cellular and global expression of specific genes related to the respective processes were examined in pectoralis major muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 66 publications
6
35
0
1
Order By: Relevance
“…Blood serum enzymes such as ALT and AST, produced mainly by the liver, can be indicators of liver disease and the overall health, particularly for obesity and other metabolic syndromes ( 34 ). Moreover, there is an increase of lipid metabolism genes associated with the development of Wooden Breast (WB) disease in broiler chickens at 3 weeks of age ( 35 ). In our study, blueberry by-products showed a significant treatment effect in lowering ALT and LIP serum concentrations during the grower phase (day 21) of broilers probably due to their compositions.…”
Section: Discussionmentioning
confidence: 99%
“…Blood serum enzymes such as ALT and AST, produced mainly by the liver, can be indicators of liver disease and the overall health, particularly for obesity and other metabolic syndromes ( 34 ). Moreover, there is an increase of lipid metabolism genes associated with the development of Wooden Breast (WB) disease in broiler chickens at 3 weeks of age ( 35 ). In our study, blueberry by-products showed a significant treatment effect in lowering ALT and LIP serum concentrations during the grower phase (day 21) of broilers probably due to their compositions.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of genes involved in lipid metabolism and uptake, such as lipoprotein lipase (LPL), fatty acid binding protein 4 (FABP4), and adiponectin c1q and collagen domain containing (ADIPOQ), in the lung tissue of WB affected broilers (Wong, 2018) is reminiscent of the transcriptomic changes associated with WB in the pectoralis major muscle (Papah et al, 2018;Lake et al, 2019) and may reflect a similar mechanism. Papah and Abasht (2019) recently found increased LPL expression in veins undergoing phlebitis in the pectoralis major muscle of WB affected birds, further substantiating the link between increased lipid metabolism and venous inflammation. In light of this knowledge, it is possible that phlebitis in the lungs is more widespread and not fully represented by the limited number of sections and samples examined in the present study.…”
Section: Histological Evaluation Of the Lungsmentioning
confidence: 69%
“…The author suggested that this expression pattern may be indicative of the progression of the disease involving regulation by some negative feedback mechanism. If disease severity and disease progression are considered more or less equivalent, a similar pattern can be seen with lipid metabolism genes, which are generally upregulated in 2-and 3-week-old birds but relatively unchanged or downregulated in 7-weekold birds Papah et al, 2018;Papah and Abasht, 2019). Due to the apparent coupling of lipid metabolism and venous inflammation, negative feedback regulation of lipid metabolism could be associated with a reduction in the innate immune response.…”
Section: Venous Inflammation and Vascular Permeabilitymentioning
confidence: 86%